Small Bowel Obstruction Caused by a Jackfruit Seed in a Patient With a History of Miles’ Operation for Rectal Cancer: The First Case Report in Vietnam - Tran Que Son; Trinh Ke Diep; Nong Ngoc Quang; Nguyen Chi Trung; Pham Anh Tuan; Vu Thi Thu; Tran Hoang Phuong Thao; Luong Thi Ngoc (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Background: Small bowel obstruction secondary to fruit seed phytobezoars is a rare clinical entity, particularly in patients with a history of major abdominal surgery. Case Report: We report the case of an 83-year-old man who presented with abdominal pain, vomiting, and a non-functioning colostomy four days after accidentally ingesting a jackfruit seed. He had a history of Miles’ operation 15 years prior for rectal cancer. Abdominal computed tomography confirmed small bowel obstruction caused by a foreign body measuring 23x31 located in the pelvis. The patient underwent emergency surgery, which was converted from laparoscopy to open laparotomy because the small bowel was densely adherent to the iliac fossa and pelvis. The jackfruit seed was successfully removed via enterotomy. Postoperatively, the patient recovered well, tolerated a regular diet, and was discharged on day 9 without complications. Conclusions: Jackfruit seed-induced small bowel obstruction in an elderly patient with surgical scarring is extremely rare. Early computed tomography, dietary caution, and a flexible surgical approach are essential to prevent complications.